RF and microwave radiation safety handbook - Kitchen, Ronald; Kitchen, Ronald (Oxford ; Boston : Newnes, 2001)
The leading professional guide to RF and microwave safety issues A practical handbook for all involved in electronic design and safety assessment, RF and Microwave Radiation Safety covers the problems of RF safety management, including the use of measuring instruments and methods, radiation hazards and risks resulting from electromagnetic interference, as well as reviewing current safety standards and the implications for RF design. The second edition takes into account a wide range of technical and legislative changes, and has been revised in line with the latest EU and international standards. Issues raised by increasing levels of microwave pollution from mobile phones and other sources are also confronted. New material covers: * International Radiological Protection Commission (IRPC): new recommendations published in 1998 * European Broadcasting Union (EBU)'s new guide * EU Physical Agents Directive and Machines Directive (both of which cover radio transmitters) * UK National Radiological Protection Board (UKNRPB) new guidance on safety levels Covers radiation hazards and risks resulting from electromagnetic interference Leading professional guide to RF and microwave safety issues Revised in line with the latest the EU and international standards.
Introduction to RF and microwave radiation -- Sources of radio frequency radiation -- Effects of radio frequency radiation -- The development of standards for human safety -- The calculation of RF field quantities -- Mobile communications systems -- RF radiation measuring instruments and methods -- X-rays and X-ray measuring instruments -- Planning surveys and measurements -- Conducting radiation measurements and surveys -- Designing to reduce radiation hazards -- Radio frequency radiation safety management and training.
"First published 1993 by Butterworth-Heinemann as RF Radiation Safety Handbook"--T.p. verso.
Includes bibliographical references (p. 422-427) and index.
Keywords: Radio frequency -- Safety measures; Radio frequency -- Physiological effect; Radiation -- Safety measures; Radiation -- Physiological effect; Microwaves -- Safety measures; Microwaves -- Physiological effect; Electronic books